2012
DOI: 10.1002/jcp.24000
|View full text |Cite
|
Sign up to set email alerts
|

CASK interacts with PMCA4b and JAM‐A on the mouse sperm flagellum to regulate Ca2+ homeostasis and motility

Abstract: Deletion of the highly conserved gene for the major Ca2+ efflux pump, Plasma membrane calcium/calmodulin-dependent ATPase 4b (Pmca4b), in the mouse leads to loss of progressive and hyperactivated sperm motility and infertility. Here we first demonstrate that compared to wild-type (WT), Junctional adhesion molecule-A (Jam-A) null sperm, previously shown to have motility defects and an abnormal mitochondrial phenotype reminiscent of that seen in Pmca4b nulls, exhibit reduced (P<0.001) ATP levels, significantly (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 56 publications
(121 reference statements)
6
53
0
Order By: Relevance
“…Thus, when WT and nulls were compared, UNCAP and CAP, the median fluorescence units for each increased ∼2-fold for nulls versus WT-sperm (Figure 5a,b). 4 | DISCUSSION 4.1 | PMCA4 and the NOSs co-localize and intimately interact in murine sperm in a Ca 2+ -dependent manner While PMCA4 (Aravindan et al, 2012;Wennemuth et al, 2003) and nNOS (Herrero, Perez Martinez, Viggiano, Polak, & Gimeno, 1996) have been localized in murine sperm on the head, over the acrosome, Figure 1a, we show that nNOS is more abundant and more widely distributed on the sperm, being found in the distal principal piece where eNOS and PMCA4 do not reside. In the present study, the pre-and post-bleaching images for the FRET data revealed the close interaction of PMCA4 and the NOSs on the sperm head, neck (Figures 2 and 3), and on the proximal principal piece of the flagellum, reflecting their co-localization.…”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…Thus, when WT and nulls were compared, UNCAP and CAP, the median fluorescence units for each increased ∼2-fold for nulls versus WT-sperm (Figure 5a,b). 4 | DISCUSSION 4.1 | PMCA4 and the NOSs co-localize and intimately interact in murine sperm in a Ca 2+ -dependent manner While PMCA4 (Aravindan et al, 2012;Wennemuth et al, 2003) and nNOS (Herrero, Perez Martinez, Viggiano, Polak, & Gimeno, 1996) have been localized in murine sperm on the head, over the acrosome, Figure 1a, we show that nNOS is more abundant and more widely distributed on the sperm, being found in the distal principal piece where eNOS and PMCA4 do not reside. In the present study, the pre-and post-bleaching images for the FRET data revealed the close interaction of PMCA4 and the NOSs on the sperm head, neck (Figures 2 and 3), and on the proximal principal piece of the flagellum, reflecting their co-localization.…”
Section: Resultsmentioning
confidence: 69%
“…There was a greater that twofold increase in fluorescence units for the median of each null population studied (Figure 4a). Jam-A null sperm were also studied for NOS activity since they have significantly reduced PMCA4 activity (Aravindan et al, 2012). In WT-sperm, NOS activity was shown to be tightly regulated at high [Ca 2+ ] c in CAP sperm, with the mean fluorescence units being <5% greater than that in UNCAP sperm.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations